2016
DOI: 10.1002/lary.26067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between 4‐MV and 6‐MV radiotherapy in T1N0 glottic cancer

Abstract: 4 Laryngoscope, 127:1061-1067, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some studies applied elective neck irradiation, and some administrated a bolus in patients with AC involvement. In 14 studies (41.2%) LC rates were not presented for the AC separately [7,8,9,10,11,12,13,14,15,16,17,18,19,20]. These studies only presented p -values, hazard ratios (HR), or odds ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies applied elective neck irradiation, and some administrated a bolus in patients with AC involvement. In 14 studies (41.2%) LC rates were not presented for the AC separately [7,8,9,10,11,12,13,14,15,16,17,18,19,20]. These studies only presented p -values, hazard ratios (HR), or odds ratios.…”
Section: Resultsmentioning
confidence: 99%
“…In 23 out of 34 (67.6%) studies in the radiotherapy group, AC involvement did not have a significant impact on LC [5,7,8,9,11,13,14,15,16,17,18,20,34,39,40,41,42,44,46,48,49,51], and in 10 studies (29.4%), it did have a significant impact [10,19,35,36,37,43,45,47,50,52]. One study (2.9%) concluded that the AC was a predictive factor for LC in T1 tumors, but not in T2 tumors [38].…”
Section: Resultsmentioning
confidence: 99%